Trees of Life - Adams, Max, 1961- (Head of Zeus, 2019)
An informative, richly illustrated book about eighty of the world's most important and remarkable trees. Our planet is home to some three trillion trees--roughly four hundred for every person on Earth. In Trees of Life, Max Adams selects, from sixty thousand extant species, eighty remarkable trees through which to celebrate the richness of humanity's relationship with trees, woods, and forests. In a sequence of informative and beautifully illustrated portraits, divided between six thematic sections, Adams investigates the trees that human cultures have found most useful across the world and ages: trees that yield timber and other materials of immense practical value, trees that bear edible fruits and nuts, trees that deliver special culinary ingredients and traditions, and trees that give us dyes, essences, and medicines. In a section titled "Supertrees," Adams considers trees that have played a pivotal role in maintaining natural and social communities, while a final section, "Trees for the Planet," looks at a group of trees so valuable to humanity that they must be protected at all costs from loss. From the apple to the oak, the logwood to the breadfruit, and the paper mulberry to the Dahurian larch, these are trees that offer not merely shelter, timber, and fuel but also drugs, foods, and fibers. Trees of Life presents a plethora of fascinating stories about them